Lipoprotein(a) measurement: challenges and opportunities - John H. Contois (Clinical Chemistry and Laboratory Medicine (CCLM), 2026)
Abstract Lipoprotein(a) [Lp(a)] is a causal, independent risk factor for atherosclerotic cardiovascular disease and calcific aortic valve stenosis. New guidelines recommend testing everyone at least once in a lifetime, and with new drugs specifically targeting Lp(a) on the horizon, accurate measurement remains vitally important. Yet, its measurement has for decades been challenging because of apolipoprotein(a) size heterogeneity, imperfect calibration strategies, and mixed use of mass (mg/dL) vs. molar (nmol/L) units. This review summarizes Lp(a) biology relevant to its measurement, current analytical approaches and their pitfalls, progress toward standardization and harmonization, including emerging mass-spectrometry–based reference measurement procedures.